Optimal inventory policy for a dynamic stochastic inventory problem with order revision - Xu, Ningxiong (Optimization letters, 2017)
A buyer wishes to satisfy independent demands for a product by ordering the product from a supplier. The buyer places an order one period before delivery and the supplier allows the buyer to revise the size of order before delivery. The buyer seeks an ordering and order-revision policy with minimum expected cost over a finite time horizon. The structure of the buyer’s optimal ordering and order-revision policy is developed under the assumptions about the ordering costs, the storage and shortage costs, and the revision that the supplier allows and the charges the supplier imposes.